2019
DOI: 10.37358/rc.19.4.7117
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Parameters in Wistar Rats Treated with Glucocorticosteroids and Vitamin E-Charged Poly Lactic-Co-Glycolic Acid (PLGA) Nanoparticles

Abstract: Glucocorticosteroids are the mainstay of treatment in many inflammatory and autoimmune disorders. Their administration can be associated with various side effects, similar to those within the metabolic syndrome. The beneficial effects of vitamin E in metabolic syndrome were demonstrated by many studies. Nowadays, vitamin E can be administrated through a new and innovative system delivery, such as polylactic-co-glycolic acid nanoparticles (PLGA-NPs). The aim of this experimental study was to compare the metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
4
1
Order By: Relevance
“…As can be seen in Table 1, dilution rate of 0.02 h -1 resulted in lactic acid with concentration of 19 gL -1 and yield of 0.75 gL -1 . The concentration of lactic acid achieved in this study is relatively higher than that reported in previous study [21], in which S. cremoris was used for fermentation of whey permeate with the concentration of 5.38 g L - 1 . In another study [22], production of lactic acid from cane molasses was investigated.…”
Section: Resultscontrasting
confidence: 60%
See 1 more Smart Citation
“…As can be seen in Table 1, dilution rate of 0.02 h -1 resulted in lactic acid with concentration of 19 gL -1 and yield of 0.75 gL -1 . The concentration of lactic acid achieved in this study is relatively higher than that reported in previous study [21], in which S. cremoris was used for fermentation of whey permeate with the concentration of 5.38 g L - 1 . In another study [22], production of lactic acid from cane molasses was investigated.…”
Section: Resultscontrasting
confidence: 60%
“…Lactic acid is recognized as a very valuable compound for its wide range of applications, from traditional uses such as chemical, soft drinks, medicine, and foodstuff, to more advanced materials such as biodegradable polymer and medical ingredients [1]. Both chemical route and fermentation process can be used to produce lactic acid; however the latter is more widely used for several advantageous reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic stress may lead to both increase and decrease in cortisol levels in general population [2,3]. Even though cortisol and its derivatives are beneficial as antiinflammatory drugs, and can be used in a variety of medical conditions [4,5], chronic emotional distress in young healthy adults persistently activates the HPA, this being translated into an exaggerated sympathetic response and cortisol increase at subjects exposed to general stressors [6,7].…”
mentioning
confidence: 99%
“…This antioxidant reduced the elevated levels of ALT and AST enzymes in ethanol treated rats [24]. Also, it was demonstrated that PLGA-NPs loaded with vitamin E had visceral tissue protective effects and lowered cholesterolemia [25].…”
Section: Resultsmentioning
confidence: 99%